Delirium and geriatric syndromes in hospitalized older patients: Results from world delirium awareness day - TUFAN ÇİNÇİN, ASLI (My University, 2022)
Objective: To determine the point prevalence of delirium and the associated risk factors in geriatric inpatients. Patients and Methods: Sixty-two hospitalized patients aged 60 years and over were recruited. The Mini Nutritional Assessment-Short Form (MNA-SF), the FRAIL scale, Katz Activities of Daily Living (ADL), and Lawton-Brody Instrumental ADL (IADL) questionnaires were administered. A delirium evaluation test (Confusion Assessment Method-CAM) was performed for diagnosing delirium. Mortality was evaluated one month after the index date. Results: The median age was 71.5 (range, 60-96) years. Delirium was detected in 29% of the patients. Frailty and dementia were associated with delirium (p<0.001 and p=0.001; respectively). Polypharmacy, indwelling urinary catheter, and low albumin were also related to delirium (p=0.025, p=0.007, and p=0.002; respectively). Age over 70 years, low Katz ADL and low MNA-SF scores were found to be independently associated with delirium in multivariate regression analysis models. The median hospitalization time was longer in the delirium group (p=0.029). Survival analysis at one month showed no significant difference between the delirium and non-delirium groups. Conclusion: Age over 70 years, impaired functionality in ADL and malnutrition were independently associated with delirium.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Delirium; Functionality; Geriatrics; Geriatric syndromes; Malnutrition; CONFUSION ASSESSMENT METHOD; POSTOPERATIVE DELIRIUM; ELDERLY-PATIENTS; FRAILTY; MORTALITY; ADULTS; CARE; ASSOCIATIONS; DEMENTIA; HEALTH; Delirium; Functionality; Geriatrics; Geriatric syndromes; Malnutrition